STRATEGI PUBLIC RELATIONS PLN UID KALTIMRA DALAM MENGELOLA AKUN INSTAGRAM @PLNKALTIMRA - Husain, Hairunnisa; Wati, Wiedya; Mellysa, Davina; Faundra, M. Fiqhry Nursayyid; Azzahra, Putri Sabina; Sherlianika, Eca (Jurnal Riset Inossa : Media Hasil Riset Pemerintahan, Ekonomi dan Sumber Daya Alam, 2024)
The rapid development of technology is utilized in the field of public relations to provide comprehensive information to the public through social media. One of them is PLN UID Kaltimra, which utilizes Instagram to disseminate information about the company through the Instagram account @plnkaltimra and applies strategic communication in account management. This research aims to find further information about how PLN UID Kaltimra uses social media platforms as a means of conveying information and communicating to stakeholders and how they handle crises or controversies through their Instagram accounts. The data analysis that the author uses is the Miles & Huberman Model of Qualitative analysis with purposive sampling techniques. The results of this research indicate that the communication strategy activities carried out by PLN UID Kaltimra’s Public Relations was helped by their Instagram platform. Implemented communication strategy through brand ambassador, sponsorship, branding, and posts about PLN’s support for IKN became an attraction for their Instagram account. Crisis management carried out by the PLN UID Kaltimra’s Public Relations communications team was also greatly helped by this Instagram platform. Apart from that, there are also several challenges faced, namely a lack of human resources managing social media accounts, a lack of understanding by team members about how social media works and its management, adjustments to the development of new algorithms and features, as well as crisis management and quick response via social media.